EVALUASI PROGRAM PELATIHAN PRODUCT KNOWLEDGE DEPARTEMEN MARKETING DELTA PADA PT PHAPROS, Tbk SEMARANG - Ruli - Kurniawati; Putut - Haribowo (Admisi dan Bisnis, 2014)
Human Resources (HR) has an important asset in a company. To develop employees competence, PT Phapros, Tbk Semarang arranges Product Knowledge training program for Delta Marketing Department employees. The department consists of Medical Sales Representative, Area Manager, and Supervisor. The training program is arranged to improve the knowledge, skill, and employees’ quality about sales detailing of Delta’s product.  In order to achieve appropriate training, it should be evaluated to see whether the training has reached target or not. Therefore, the purposes of this research were to analyze the result of  participants’ reaction about the Product Knowledge training programand to evaluate the result of participant’s learning based on post-test and pre-test. This research was descriptively analysis written. The method of collecting the data were interview and literature study. The data used are the primary, secondary in the form of qualitative and quantitative data. The techniques of analysis used are descriptive statistic and wilcoxon signed rank test. SPSS version 16.0 is used to process the data.The result of the research shows that the evaluation results in reaction level, the participants give a good assesment to training’s factors, such as material, trainer, facilities, and committe’s service. Then, learning evaluation shows the change in knowledge as a result of the training. Knowledge improvement is shown from wilcoxon test with Z value of -5.379  and significant value is 0,000. The test shows that there is a difference between pre-test and post test. PT Phapros, Tbk Semarang can use these results as a reference in order to improve the implementation of further product knowledge training program.